Disposition of tris(4-chlorophenyl)methanol and tris(4-chlorophenyl)methane in male and female Harlan Sprague Dawley rats and B6C3F1/N mice following oral and intravenous administration. (3rd April 2019) - Catlin, Natasha R.; Waidyanatha, Suramya; Black, Sherry R.; Mathews, James M.; Snyder, Rodney W.; Patel, Purvi R.; Watson, Scott L.; Fennell, Timothy R.
Abstract: Tris (4-chlorophenyl)methane (TCPME) and tris (4-chlorophenyl)methanol (TCPMOH) have been detected in various biota and human tissues. The current studies were undertaken to investigate the disposition and metabolism of TCPME and TCPMOH in rats and mice. [ 14 C]TCPME was well absorbed (≥66%) in male rats and mice following a single oral administration of 1, 10, or 100 mg/kg. The excretion of [ 14 C]TCPME-derived radioactivity in urine (≤2.5%) and feces (≤18%) was low. The administered dose was retained in tissues (≥ 64%) with adipose containing the highest concentrations. The metabolism of TCPME was minimal. The disposition and metabolism of [ 14 C]TCPME in females was similar to males. The time to reach maximum concentration was ≤7 h, the plasma elimination half-life was ≥31 h, and the bioavailability was ≥82% following a 10 mg/kg oral dose of [ 14 C]TCPME in male rats and mice. The disposition of [ 14 C]TCPMOH was similar to that of [ 14 C]TCPME. Following an intravenous administration of [ 14 C]TCPME or [ 14 C]TCPMOH in male rats and mice, the pattern of disposition was similar to that of oral administration. In conclusion, both TCPME and TCPMOH are readily absorbed and highly bioavailable following a single oral administration pointing to importance of assessing the toxicity of these chemicals.